Children as Internet users: how can evidence better inform policy debate?. Issue 1 (2nd January 2017) - Byrne, Jasmina; Burton, Patrick
ABSTRACT: As more and more researchers from all over the world are becoming interested in how children use the Internet and mobile technologies, global evidence of both the opportunities that the Internet brings, and their associated risks, is increasing. A new research initiative, Global Kids Online, contributes to this through provision of tools and guidelines to national researchers and comparative analysis of country-specific research findings. For the first time, rigorous and comparable evidence from lower and middle-income countries (South Africa, Serbia, the Philippines, Brazil and Argentina) is available on a range of topics: children's civic engagement, participation and digital literacy, as well as risky behaviour and negative experiences. But to what extent do current Internet-related or broader child rights policies (regarding education and protection) correspond to this growing evidence base? What are the opportunities, through evidence use, for influencing new policy direction related to children and the Internet? Drawing on recent research and an associated policy review, this paper explores the link between the two and provides some suggestions for policy and questions for further discussion.